2010
DOI: 10.1007/s00484-009-0290-8
|View full text |Cite
|
Sign up to set email alerts
|

Excess deaths during the 2004 heatwave in Brisbane, Australia

Abstract: The paper examines whether there was an excess of deaths and the relative role of temperature and ozone in a heatwave during 7-26 February 2004 in Brisbane, Australia, a subtropical city accustomed to warm weather. The data on daily counts of deaths from cardiovascular disease and non-external causes, meteorological conditions, and air pollution in Brisbane from 1 January 2001 to 31 October 2004 were supplied by the Australian Bureau of Statistics, Australian Bureau of Meteorology, and Queensland Environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 35 publications
2
51
1
Order By: Relevance
“…This is the first study oF heat illness and ED visits associated with heatwaves in Brisbane, and complements previous work on the effects of heat on mortality, hospital admissions and ambulance utilisation in this subtropical climate [13-16]. Our results show that as the temperature increased so did the likelihood by all gender and age groups of attending EDs with heat-related illness.…”
Section: Discussionsupporting
confidence: 79%
“…This is the first study oF heat illness and ED visits associated with heatwaves in Brisbane, and complements previous work on the effects of heat on mortality, hospital admissions and ambulance utilisation in this subtropical climate [13-16]. Our results show that as the temperature increased so did the likelihood by all gender and age groups of attending EDs with heat-related illness.…”
Section: Discussionsupporting
confidence: 79%
“…Warmer climates also typically show relatively small daily temperature variations in comparison with temperate climates, and heat effects tend to be smaller than those in the temperate locations (Anderson and Bell 2009). Our results and other recent findings have shown, however, that even in warmer climates the population demonstrates an elevated risk of mortality during unusually hot days and that a relative measure seems to be a better predictor of the heatrelated vulnerability than an absolute measure (Gouveia et al 2003;Anderson and Bell 2009;Chau et al 2009;Tong et al 2010;Yu et al 2010). Even though several measures of thermal stress were used in previous studies (Basu et al 2008;Zanobetti and Schwartz 2008;Papanastasiou et al 2010), a systematic assessment of the performances of these indices at a single location has rarely been conducted.…”
Section: Discussioncontrasting
confidence: 47%
“…Heat stress is a significant health concern and has been previously associated with substantial excess mortality (e.g., Fouillet et al 2006;Smargiassi et al 2009), as has been documented during heat waves in Europe, the United States, and Australia (e.g., Semenza et al 1996;Fouillet et al 2006;Tong et al 2010). Previous studies have used a variety of heat stress measures (e.g., maximum and minimum temperatures, apparent temperature, and biometeorological and human comfort indices) to assess the vulnerability of populations to heat stress (e.g., Hö ppe 1999; Spagnolo and de Dear 2003;Nicholls et al 2008;Barnett et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We did not control for the potential confounding effects of air pollution (eg, ozone), as these data were not complete for the whole study period in all three cities. However, previous studies have reported the health impacts of a heatwave as occurring independent of air pollution 10 33. A relatively small number of heatwave days may explain why the differences in heat effects between the three cities as well as the subpopulations were not statistically significant as their 95% CIs were overlapped each other.…”
Section: Discussionmentioning
confidence: 88%